Artificial intelligence in medicine : knowledge representation and transparent and explainable systems : AIME 2019 International Workshops, KR4HC/ProHealth and TEAAM, Poznan, Poland, June 26-29, 2019, Revised Selected Papers /: knowledge representation and transparent and explainable systems : AIME 2019 International Workshops, KR4HC/ProHealth and TEAAM, Poznan, Poland, June 26-29, 2019, Revised Selected Papers. (2019) - Unknown
No abstract available